PENGOLAHAN LIMBAH ORGANIK UNTUK PEMBUATAN PUPUK KOMPOS DI DESA KERSIK KECAMATAN MARANGKAYU - Sari, Anisa Sasmita; Nurlita, Febi; Bharata, Wira; Wahyuni Arsyad, Annisa; Hijrah, Lailatul (Jurnal Pengabdian Masyarakat Polmanbabel, 2024)
This training activity is part of a series of efforts to manage organic waste with the aim of producing compost fertilizer in the Kersik Village area, Marangkayu District. Using participatory research methods, this training documents the main processes in managing organic waste from local sources. The focus includes the natural fermentation techniques used as well as assessing the quality and yield of the compost produced. In addition, this activity considers the active involvement of local communities in implementing environmentally friendly waste management practices. The analysis carried out includes technical aspects of the waste composting process as well as exploration of the social, economic and environmental impacts this initiative has on the welfare of local communities as well as efforts to reduce negative impacts on the environment. By holding this training activity, it is hoped that it can provide useful insights in strengthening sustainable organic waste management strategies in Kersik Village, while also contributing to efforts to maintain the sustainability and welfare of the local community.